Connecting Legend and Science through Geomythology: Case of Langkawi Unesco Global Geopark - Tanot Unjah; Sharina Abdul Halim (Kajian Malaysia, 2017)
Integrating scientific and cultural knowledge is pivotal in the conservation of a geopark. Using case study from the Langkawi UNESCO Global Geopark, the main aim of this article is to discuss the connection between scientific aspects of geological landscape and myths, legends and folklore in the area (or also known as geomythology). Langkawi's geological landscape comprises five key rock formations known as Machincang, Setul, Singa, Chuping and igneous rock of Gunung Raya. Each formation consists of exposed rock diversity that resulted from tectonic activity and weathering process caused by waves and surface runoff water. Langkawi's geological landscapes are bestowed with distinctive rock diversity that hold within them mysterious legends, myths and folklore, in which connect local communities with landscapes. Among the well-known geomythology, or legends associated within these geological landscapes, are Gunung Machinchang, Gunung Raya and Belanga Pecah (Battle of the Giants of Mat Chinchang and Mat Raya), Gua Cherita (Legend of The Roman Emperor's Son and mythical giant bird) and Pulau Dayang Bunting (Tale of A Pregnant Maiden). The interpretation of landscape from a scientific perspective together with cultural knowledge has revealed an intrinsic link between geology and its people. In a sense, geomythology carries great significance to geopark development, not only for conservation purpose but it also serves as a means to boost local tourism that can in turn facilitate the local socio-economic development of the island.